FENOMENA OPERASIONAL PERBANKAN SYARIAH DI ERA DIGITAL: ANALISIS KUALITATIF BERBASIS LITERATUR TENTANG KUALITAS LAYANAN, MOBILE BANKING, PEMASARAN MEDIA SOSIAL, DAN TATA KELOLA KEPATUHAN SYARIAH - Karina Andari; Mochammad Alfuad Febrian; Danang Permadi (LPPM INSTITUT AGAMA ISLAM HASANUDDIN PARE, 2026)
Digital transformation has reshaped Islamic banking operations, ranging from branch-based service quality to app-based services such as online account opening and mobile banking. At the same time, rapid digital innovation requires stronger sharia compliance governance so that sharia principles are embedded in business processes rather than remaining a mere label. This article synthesizes previous studies through a qualitative thematic review to map key operational phenomena in the digital era that are relevant to user experiences, particularly students and the wider community. The review covers themes on service quality and customer satisfaction/loyalty, digital onboarding, mobile banking adoption and behavioral impacts, social media marketing, and sharia governance (SSB/DPS roles, sharia division, and sharia non-compliance risk). The synthesis indicates that satisfaction and usage intention are driven by system reliability, security, service responsiveness, and educational communication, while trust is reinforced by effective mechanisms of sharia oversight. Implications highlight the need to integrate digital service strategy, educational social media content, and institutional strengthening of sharia compliance structures to support the sustainability of Islamic banking.